Особенности механизмов защиты и акцентуаций характера личности, склонной к гелотофобии [Articol] - Постолатий, Екатерина (CEP USM, 2013)
This article is describing the problem of gelotofobia – fear to be laughed at, and its manifestations in human character and behavior. Basing on the analysis of existing psychological literature, is widened the integral concept of gelotophobia, and individual-typological features of a person, prone to gelotofobia. In this research the problem gelotofobia is described in its relation with the manifestations of accentuations of character and specifics in the usage of defense mechanisms. The obtained empirical data can be used by psychologists and educators in counseling individuals who are prone to gelotofobia.
Keywords: психологическая защита